INTEGRATING ART THERAPY IN SCHOOLS: A SYSTEMATIC LITERATURE REVIEW - ABRAMOVSKI, Gal; MEYTAL, Fogel Simhony (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2019)
Art therapy is a method of treatment that involves the mental world of human beings. The purpose of this therapy is to improve the patient's emotional and physical functioning and condition. Art therapy is utilized for emotional and mental problems and as a diagnostic tool. This therapeutic technique is currently common in a wide variety of settings in varied therapeutic and rehabilitative settings such as: educational settings, hospitals and mental health centres. With regard to interventions implemented within schools, the significance and comprehension of art therapy is lacking. The purpose of this study is to identify the variety of interventions that exist in the literature on integration of art therapy in schools. Furthermore, this article will present the methods of evaluation, the results, as well as factors that influence the existence of this intervention. The results of the systematic review might be useful for continuing and expanding the integration of art therapy within schools.